Bioconversion of Tuna Processing Waste into Fish Sauce - Ngmenlanaa, S. (University of Ghana, 2002)
Fish sauce is a fermented fish product. It is a liquid extract of fish tissues produced by fermenting fish and/or fish processing by-products, sometimes mixed with a carbohydrate source, under a salt-saturated condition. It is typical of the oriental countries where it is consumed as a condiment. Analysis of a typical fish sauce suggests varying degree of hydrolysis of the proteins and other macromolecules of the fish, which are typical of microbial and enzymatic actions, although the high salt concentration is very restrictive to the growth of many microorganisms. The purpose of the work was to investigate the feasibility of producing fish sauce using some tuna processing wastes and the physico-chemical and microbiological changes associated with the biodegradation of tuna tissues in the production of the sauce. Tuna processing wastes obtained from a cannery were characterized physically (by determining the proportions of bones and flesh), physico-chemically and microbiologically. Sub-samples of the tissues were then formulated into appropriate media, adding glucose and sodium chloride (at predetermined concentrations) and fermented for the production of the sauce. The yield of sauce, the physico-chemical changes of the substrate and the microfloral characteristics of the fermentation were determined. The effect and the type of the carbohydrate used on the yield and quality of the sauce were also investigated. The tuna waste comprised of 80-94% soft tissues, 4.2-18.9% bone and 1.2-1.6% of fins. The proximate composition was as follows: protein, 21.24 - 23.41 %, crude fat 2.17 - 2.54 %, total ash 3.76 - 9.24 % and moisture 67.09 - 76.81 %. The microbial counts were l.OxlO7 - 5.4xl09 cfu/ml aerobic mesophiles, 5.1xl06 - 8.51xl08 facultative anaerobes and l.OxlO3 - 9.3xl03 yeasts. The pH and the moisture content of the extracts produced during the fermentation fell as the fermentation period increased, from 5.64 to 4.45 and 83 % to 73%, respectively. The salinity of the extract however, increased from 10.1 to 16 %. The total protein and free amino nitrogen content of the extract ranged from 11.2 tol8.0 % and 5.0-8.3 to 6.4-36.6mg/ml respectively. The titrable acidity increased from 0.9-1.0 to 1.2-2.5 %, whilst total lipids content ranged from 2.3 and 4.0 %. The yield of extract produced (sauce) over the fermentation period ranged from 128 - 295 ml per kg of fermenting mixture. Generally, the physico-chemical characteristics of the sauce produced using glucose as the carbohydrate source were comparable to literature values. Heavy metals were also not detected beyond their permissible levels. Histamine levels ranged from 13.95 - 34.41 ppm, far below the recommended maximum permissible level of 50 ppm. SDS-gel electrophoretograms of samples of the fish extract taken at various times during fermentation showed a consistent and gradual degradation of macro protein molecules. The test for presence of pathogens was negative in all samples. The predominant bacteria isolated during the 49-day period were: Micrococcus, Planococcus, Corynebacterium, Peptococcus, Streptococcus, Staphylococcus, Bacillus Moraxella and Branhamella spp. The predominant yeasts were Pichia capsulata, Candida vaccinii, Rhodotorula becarum, Rhodotorula pustula, and Sporobolomyces roseus. Some of these, particularly the Bacillus and Staphylococcus spp. demonstrated high proteolytic activity. It maybe concluded that fish sauce could be processed from tuna processing wastes through a bioconversion process.
Thesis(M.Phil)-University of Ghana,2002.